Multicultural Islamic Education as an Indicator of Religious Moderation in Indonesia - Zalnur, Muhammad; Basit, Abdul; Nelwati, Sasmi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Moderate religiosity in Indonesia is not widely accepted, owing to the existence of factors such as religious liberalization and secularization. The purpose of this study is to identify the level of multilingual Islamic education in Indonesia using the moderation indicator recommended by the Ministry of Religion. This study employs a philosophical normative approach. The theory of analysis used is Azyumardi Azra's multicultural Islamic education. The study's findings reveal a dimension of multicultural Islamic education in Indonesia's three moderate indicators. To begin, the value of education is based on indicators of tolerance in the development of Islamic knowledge and social skills that reflect the realities of human life. Second, the value of education is based on the commitment to learning about Islam and its social aspects, which promotes peace and stability in daily life. Third, humanism in education is reflected in anti-radicalization indicators in the social and cultural development of Islam, which combines with humanism. Also, the nilai pendidikan wasatiyah in the indicator of local accommodations with regard to local culture in fostering social and cultural adherence to Islam is moderate enough to embrace local traditions while remaining non-complementary to Islamic education. The implications of this research theory state that there is relevance of universal values in Indonesian moderation indicators with various multicultural Islamic education values.